2008
DOI: 10.1186/1471-2334-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV, HBV, HCV and syphilis infections among prison inmates and officers in Ghana: A national multicenter study

Abstract: Background: Prisons are known to be high-risk environments for the spread of bloodborne and sexually transmitted infections. Prison officers are considered to have an intermittent exposure potential to bloodborne infectious diseases on the job, however there has been no studies on the prevalence of these infections in prison officers in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
10
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(147 citation statements)
references
References 53 publications
10
103
10
18
Order By: Relevance
“…Seidman's (1969, p. 431) comment that the Ghana penal system "stands as monument to colonial rule, as a memorial to confused goals, conflicting objectives, policies evolved and abandoned, and sometimes, no policies at all" remains relevant today. For instance, Ghana's penal system as it was under British colonial rule has remained virtually unchanged in terms of its paramilitary structure of administration coupled with inadequate training and compensation for officers, inadequate infrastructure and widespread infectious diseases, its emphasis on traditional custodial functions (i.e., security and discipline in its operations), and the maintenance of a policy of safe custody of prisoners and trade training when practicable (Adjei et al, 2008;Akoensi, 2014;Ghana Prisons Service, 2010;Mendez, 2014;Prisons Service Decree, 1972 [NCRD 46]). Despite the insistence on vocational training for offenders (officially referred to as "trade training" by the GPS, and also a legacy of colonialism), no empirical study exists to ascertain whether such training reduces recidivism or is beneficial to the prisoners' wellbeing.…”
Section: The Research Contextmentioning
confidence: 99%
“…Seidman's (1969, p. 431) comment that the Ghana penal system "stands as monument to colonial rule, as a memorial to confused goals, conflicting objectives, policies evolved and abandoned, and sometimes, no policies at all" remains relevant today. For instance, Ghana's penal system as it was under British colonial rule has remained virtually unchanged in terms of its paramilitary structure of administration coupled with inadequate training and compensation for officers, inadequate infrastructure and widespread infectious diseases, its emphasis on traditional custodial functions (i.e., security and discipline in its operations), and the maintenance of a policy of safe custody of prisoners and trade training when practicable (Adjei et al, 2008;Akoensi, 2014;Ghana Prisons Service, 2010;Mendez, 2014;Prisons Service Decree, 1972 [NCRD 46]). Despite the insistence on vocational training for offenders (officially referred to as "trade training" by the GPS, and also a legacy of colonialism), no empirical study exists to ascertain whether such training reduces recidivism or is beneficial to the prisoners' wellbeing.…”
Section: The Research Contextmentioning
confidence: 99%
“…Studies carried out in several countries, including Brazil, showed a high prevalence of HIV and syphilis infections in incarcerated men 3,5,10,11,12,13 and women 2,3,6,14,15,16,17,18,19,20,21 , reinforcing the importance of serological diagnosis in prisons for the implementation of available intervention. However, Brazilian studies have been carried out in isolated prison units.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics, together with the condition of being incarcerated in crowded conditions, have resulted in an elevated prevalence of viral hepatitis infection [1][2][3][4][5][6][7][8][9]. It was estimated that, in the prison population in Spain, the prevalence of HCV infection was between 38.2 and 48% [10][11][12][13] and that of VHB surface antigen (HBsAg) was approximately 3.8% [12].…”
Section: Introductionmentioning
confidence: 99%